Analysis of clavicle fractures tendency in three Lima hospitals - Quispe, Antonio (2015)
Introduction: Clavicle fracture rate is one of the most visible indicators of institutional birth attendance quality. Its analysis will allow interventions on impact evaluation for direct benefit of our patients. Objective: To determine the clavicle fracture rate tendency in three Lima, Peruvian hospitals. Design: Ecological type study. Institutions: San Bartolome and Santa Rosa Hospitals, and Instituto Especializado Materno Perinatal, Lima, Peru. Participants: Newborns. Interventions: Individual and global analysis of each institutional perinatal informatic system monthly reports, from January 2004 through December 2008, on the chronological evolution of clavicle fracture rate, in order to determine its tendency and characteristic profiles. Main outcome measures: Clavicle fracture rates (total clavicle fractures per month * 100/ total deliveries per month). Results: During the study period the highest clavicle fracture rate was registered at IEMP (2,58% ± 0,32%), and San Bartolome (1,03% ± 0,53%, p<0,01) and Santa Rosa (0,72% ± 0,21%, p<0,01) Hospitals maintained significantly lower rates. Though, analysis of the annual progression of these rates showed clavicle fractures were decreasing at both IEMP (2,20% [2004], 2,93% [2006], 2,29 [2008]) and Santa Rosa Hospital in the last three years, but San Bartolome’s rate increased from 0,47% to 1,76% in the last five years. Conclusions: IEMP fracture rate is much higher than in Santa Rosa and San Bartolome Hospitals; but in the last three years this rate decreased consistently at IEMP and Santa Rosa Hospital, and is increasing at San Bartolome Hospital.